2015
DOI: 10.1007/s00228-015-1954-4
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate prescribing in community-dwelling older people across Europe: a systematic literature review

Abstract: PIP prevalence in European community-dwelling older adults is high and depends partially on the data collection method used. Polypharmacy, poor functional status, and depression were identified as the most common risk factors for PIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
240
4
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(282 citation statements)
references
References 91 publications
31
240
4
7
Order By: Relevance
“…Moreover, we added 3 criteria (assessing potentially inappropriate prolonged use of medications) to those of the Laroche list, which happened to increase by nearly 10% the prevalence of PIMs. Consistently with the review by Tommelein et al [23], we found benzodiazepines and NSAIDs among the most reported PIMs. Conversely, inappropriate use of antidepressants was limited in our study.…”
Section: Prevalence Of Polypharmacy and Pimssupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, we added 3 criteria (assessing potentially inappropriate prolonged use of medications) to those of the Laroche list, which happened to increase by nearly 10% the prevalence of PIMs. Consistently with the review by Tommelein et al [23], we found benzodiazepines and NSAIDs among the most reported PIMs. Conversely, inappropriate use of antidepressants was limited in our study.…”
Section: Prevalence Of Polypharmacy and Pimssupporting
confidence: 93%
“…Our estimates of the prevalence of polypharmacy and PIMs are relatively high compared to previous estimates [7,9,11,23], which was expected considering our methodology. Indeed, the prevalence of polypharmacy should be considered with regard to our definition that encompasses all the medications prescribed over 3-month periods.…”
Section: Prevalence Of Polypharmacy and Pimssupporting
confidence: 62%
“…Moreover, polypharmacy is associated with poor adherence, lower physical and social function, higher healthcare costs, and decreased quality of life [13,16,19]. Additionally, inappropriate prescribing, including both over-(potentially inappropriate prescribing [PIP]) and underprescription (potential prescribing omission [PPO]) is also associated with poor outcome, such as increase in adverse drug events [21]. While polypharmacy is relatively well defined, the definition of multimorbidity is not consistent in the literature; a common definition is 2 or more comorbidities [3].…”
Section: Introductionmentioning
confidence: 98%
“…Some researches related to polypharmacy used this classification system 12. ATC classification contains all kinds of medications and we can interpret each classification as those effects in the body.…”
Section: Methodsmentioning
confidence: 99%